Information System of Staple Material Sales in Website-Based Online on Tulangan Market (Case Study: Pak Latief's Shop) : Sistem Informasi Penjualan Bahan Pokok pada Pasar Tulangan secara Online Berbasis Website (Studi Kasus : Toko Pak Latief) - Mulyansyah , Muhammad Febri; Astutik, Ika Ratna Indra (JOINCS (Journal of Informatics, Network, and Computer Science), 2023)
Developments in the economic sector so far have had quite rapid consequences in the business world, this has resulted in differences in sales at the market level. The market itself is a meeting place for buyers and sellers to make buying and selling transactions of goods or services. Tulangan Market is a traditional market located in the District of Tulangan, Sidoarjo Regency, East Java Province. In the Reinforcement Market there are several types of sellers such as retail traders, wholesalers and kiosks which are scattered in almost all corners of the market. The Tulangan market is also not much different from markets in general which sell daily needs such as food ingredients in the form of fish, fruit, vegetables, eggs, meat, cloth, electronic goods, services, etc. Besides that, it also sells traditional cakes and other Indonesian food. Not all traders in the Reinforcement Market can carry out the buying and selling process freely, especially during erratic rainfall. This creates problems in the sales process factors for traders. After knowing this problem, the author wishes to help traders who do not have their own trading area so that they can run their business stably and smoothly. With the current rapid world of technology, the authors hope that traders can use web pages that are familiar to many people to alleviate their problems through the "Website-Based Market Information System Case Study of the Sidoarjo Tulangan Market".